Using epistemic instructional activities to support secondary science teachers' social construction of knowledge of anthropogenic climate change during a professional learning experience. Issue 4 (11th October 2022) - M. Zummo, Lynne; J. Dozier, Sara
Abstract: This article describes an innovative intervention used within a professional learning experience (PLE) for early-career high school science teachers. The intervention aimed to develop participants' conceptual understanding of climate change while supporting engagement in learning via scientific practices through use of epistemic instructional activities. Participants were 18 teachers from 16 different public schools across the US, all serving historically underserved student populations. The intervention consisted of a sequence of three learning experiences, each of which engaged participants in learning through a unique epistemic tool or activity. We describe each activity and offer examples of our developed materials. Additionally, we use qualitative coding to analyze teacher-produced artifacts to evaluate the intervention. Results show: 1) a data analysis epistemic activity supported learner attention to variation in climate data; 2) an explanation-focused epistemic activity supported integration of several concepts within social constructions of mechanistic explanations; and 3) a claims evaluation epistemic activity supported participants' linking of concepts about variation to mechanistic explanations of climate change, as well as their understanding of argumentation in general. We suggest that other educators could benefit from adapting our intervention to meet the needs of their contexts. Supplemental data for this article is available online at https://doi.org/10.1080/10899995.2021.1986785 .